The Process and Policy Challenges of Adapting and Implementing the Early Development Instrument in Australia - Goldfeld, S.; Sayers, M.; Brinkman, Sally; Silburn, Sven; Oberklaid, F. (Lawrence Erlbaum Associates, 2009)
Research Findings: Australian state and federal governments have increasingly recognized early childhood as a critical period for investing in interventions. At the same time, a number of organizational, structural, and environmental responses have been put in place to build the capacity of communities to better support children and their families. It was in this policy environment of increasing investment in community- level interventions to promote outcomes for children that the need emerged in Australia for a population measure of early childhood development. This article outlines some of the process and policy challenges associated with the introduction and adaptation of a population measure of early child development—the Early Development Instrument (EDI)—by Australian communities, which culminated in its adoption as a national measure of early childhood development in 2008. It highlights the need to develop both a strategic and psychometric approach to successfully implement any measure that requires community-wide participation. Practice or Policy: There were particular challenges to embedding the AEDI, and therefore data about early childhood developmental outcomes, within policy processes. These are discussed in terms of the adaptation and validation process in Australia, the development of novel methods of data collection for national implementation, the benefits of cross-national comparisons, and the policy impact and environment that has been necessary for longer term sustainability.